Crystal structure determination of the armadillo repeat domain of Drosophila SARM1 using MIRAS phasing. Issue 10 (4th October 2021) - Gu, Weixi; Luo, Zhenyao; Vonrhein, Clemens; Jia, Xinying; Ve, Thomas; Nanson, Jeffrey D.; Kobe, Bostjan
Abstract : The cystallization and structure determination of the armadillo repeat domain of Drosophila SARM1 are described. The phase problem was solved using the MIRAS technique with autoSHARP, combining diffraction data from native, selenomethionine‐labelled and bromide‐soaked crystals. Abstract : The crystal structure determination of the armadillo repeat motif (ARM) domain of Drosophila SARM1 (dSARM1 ARM ) is described, which required the combination of a number of sources of phase information in order to obtain interpretable electron‐density maps. SARM1 is a central executioner of programmed axon degeneration, a common feature of the early phase of many neurodegenerative diseases. SARM1 is held in the inactive state in healthy axons by its N‐terminal auto‐inhibitory ARM domain, and is activated to cleave NAD upon injury, triggering subsequent axon degeneration. To characterize the molecular mechanism of SARM1 activation, it was sought to determine the crystal structure of the SARM1 ARM domain. Here, the recombinant production and crystallization of dSARM1 ARM is described, as well as the unconventional process used for structure determination. Crystals were obtained in the presence of NMN, a precursor of NAD and a potential activator of SARM1, only after in situ proteolysis of the N‐terminal 63 residues. After molecular‐replacement attempts failed, the crystal structure of dSARM1 ARM was determined at 1.65 Å resolution using the MIRAS phasing technique with autoSHARP, combining data from native, selenomethionine‐labelled and bromide‐soaked crystals. The structure will further the understanding of SARM1 regulation.